The Dispositif of Terror: Islamic State, Biopolitical Governance, and the Digital Conjuncture - Rarm, Lewis (Auckland University of Technology, 2021)
This thesis re-conceptualises contemporary articulations of terrorist governance through Gilles Deleuze and Felix Guattari’s (D&G herein) concept of assemblage, and Michel Foucault’s theories of dispositif (dispositive, apparatus) and biopower. It unpacks the media and governmental strategies of the group known as the Islamic State (IS) by teasing out the resonance between the group’s internal administrative processes, external media output, and its supporters’ social media discourse. A consideration of IS’s social ontology as an assemblage, and their terroristic conduct through Foucault’s dispositif, seeks to problematise the group as more than just a terrorist organisation. Rather, an analysis of globally fluid and conjunctive terrorist strategies executed via media, governance, and conduct, as part of and produced by a dispositif, accounts for intersections of social power, epistemology, production, circulation, function, a/effects, and the techno-discursive moment from which the group emerge and reside. Taking both media and administration as my objects of study, I consider how IS’s articulations of terror, in terms of media and governance, constitute what Foucault called a dispositif. That is, to what extent was IS’s media and governmental strategy, and its implementation, composed of ‘a heterogeneous ensemble consisting of discourses, institutions, architectural forms, regulatory decisions, laws, administrative measures, scientific statements, philosophical, moral and philanthropic propositions’? (Foucault 1980, p. 194). I argue that to understand the group more holistically, as well as how contemporary terrorist groups produce subjects through local and global concentrations of governance, an analysis of both their administration and media is necessary. To achieve this, I conduct a dispositif analysis (Jäger & Maier 2009, 2016; Caborn 2007). A dispositif analysis, essentially a tripartite discourse analysis of texts, actions, and objects, has a pronounced focus on the materiality of discourse which this thesis seeks to address within the context of IS’s activities. Specifically, I analyse internal administration documents used in an official capacity in the caliphate, media produced in English directed outside the caliphate, and social media content produced by IS supporters. My analysis bears a number of conclusions. There is strong discursive continuity across IS media and governance which was retained over time. That is, IS have a strong sense of in-group identity and a discursive worldview that is very rigid. IS govern through the logic of the biopolitical which I show to be a dominant mode of power in IS media and administration. As well, by putting theorists of dispositif and discourse theory into conversation, I develop and show dispositif analysis to be both a productive methodological device for conceptualising an object of study, as well as its own mode of analysis. Following a reflection on the ongoing resilience of IS online, I ultimately locate IS within the mediatisation of terrorism: the increasing extent to which acts of terror are mediated by terrorists themselves.
Keywords: Islamic state; Foucault; Deleuze; Guattari; Assemblage; Terrorism; Media studies; Biopolitics; Dispositif; Apparatus; Power; Social media; Twitter; Governance; Governmentality